Salivary Biomarkers in the Diagnosis of Periodontitis - Imrana Tanvir, Madiha Ehsanulhaq, Hamna Salahuddin, Amber Hassan, Fatma Ibrahim Albeladi, Aimen Zulfiqar, Shymaa A. Elaskary, Samah Said Elbasateeny (Pakistan Journal of Medical & Health Sciences, 2022)
Periodontitis is caused by complex interactions among the host immune system and the subgingival microbiota, which causes damage to periodontal ligament attachment, and tooth loss. The impacts of periodontitis are highly significant. In the last few decades, periodontitis has enhanced the economic burden globally because it is associated with various other systemic diseases and the relative treatment is expensive. The prevalence of the periodontal disease varies in different countries of the world, with a higher prevalence reported in Asian countries. Traditional clinical methods for diagnosing and monitoring periodontitis are inadequate for anticipating patient sensitivity, disease activity, and treatment responses. Several disease-specific molecular biomarkers have been identified as a result of periodontitis immunopathogenesis studies and saliva mediator analyses. Assessments of these salivary biomarkers will yield more accurate diagnostic results, supporting the clinical management of patients. The discovery of these salivary biomarkers highlights salivary diagnostics by introducing quick, non-invasive, screening procedures. Finally, the development of sensitive and specific disease biomarkers will yield highly validated results and aid in the clinical management of periodontitis patients Keywords: Periodontitis, Cytokines, Diagnosis, Salivary Markers